DELEGITIMASI SURAT WASIAT ANAK ANGKAT (Studi Kasus Putusan Mahkamah Agung RI. No.311 K/PDT/1996) - Dian Rahmat Nugraha (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
Abstract. This research is about the practice of adoption of children among Indonesian society which is carried out by couples who are married but do not have children. This study aims to determine the legal status of adopted children, in consideration of judges, review of Islamic and customary law on these decisions. This research framework is based on the concepts and theories of Islamic law. As a big theory for the concept of justice, at the next level the theory of maqashid al-sharia and the operational level uses the istinbath al-ahkam (aplicative) theory. This research method uses normative juridical methods. Collecting data through library research and field research. The research concludes that the principle of adoption according to Islamic law is childcare with the intention that a child does not become neglected and grows and develops both physically and mentally. Regarding this, Islam does not prohibit the provision of various forms of livelihood assistance to adopted children; Judges 'considerations are based on juridical, sociological and philosophical grounds and judges' legal considerations at the Supreme Court are based solely on juridical basis. Islam views that the decision of the Supreme Court is inconsistent because it does not adhere to elements of justice and legal certainty. Keywords: wasiat wajibah, adopted child, inheritance